(untitled) (Research, Society and Development, 2020)
Mutation is a topic rarely addressed in high schools, due to factors such as the complexity of understanding the content. However, this theme is of great importance in broad biological processes, as it serves as a starting point for different discussions such as environmental health, genetics and evolution. As a teaching possibility, the development of experimental protocols that are easy to apply is considered a tool that helps in the articulation of abstract contents. Therefore, the objective of this work was to describe an experimental methodology to assist in the teaching of mutation in schools. As a methodology, the practice was formulated from the adaptation of the micronucleus test, widely used in the area of mutagenesis. The adaptation sought to use materials and methods easily accessible to teachers from the basic network. As a result, the adaptation of the micronucleus assay was applied to high school students and obtained promising results in a school located in the state of Rio Grande do Sul. Among the results, it should be highlighted the basic notions of what mutations are and the problem of an unhealthy environment in relation to the mutagenesis process. It was concluded that the micronucleus assay in schools proved to be a practical alternative for discussions about mutation in schools. However, further studies are needed to develop tools and elucidate the importance of discussing the topic in basic education.